Grapes and their derivatives in modulation of cognitive decline: a critical review of epidemiological and randomized-controlled trials in humans. Issue 4 (21st February 2021) - Restani, Patrizia; Fradera, Ursula; Ruf, Jean-Claude; Stockley, Creina; Teissedre, Pierre-Louis; Biella, Simone; Colombo, Francesca; Lorenzo, Chiara Di
Abstract: With an increase in life expectancy, the incidence of chronic degenerative pathologies such as dementia has progressively risen. Cognitive impairment leads to the gradual loss of skills, which results in substantial personal and financial cost at the individual and societal levels. Grapes and wines are rich in healthy compounds, which may help to maintain homeostasis and reduce the risk of several chronic illnesses, including dementia. This review analyzed papers that were systematically searched in PubMed, MEDLINE, Embase, and CAB-Abstract, using the association between grapes (or their derivatives) and their effects on cognitive functions in humans. Analysis was restricted to epidemiological and randomized-controlled studies. Consumption of grape juice (200-500 mL/day) and/or light-to-moderate wine (one to four glasses/day) was generally associated with improved cognitive performance, while the results for other alcoholic beverages were controversial and inconclusive. Bioactive molecules contained in grapes and wine were also considered, with particular attention paid to resveratrol. Due to the relatively high doses required (150-1000 mg/day) for bioactivity coupled with its low bioavailability, resveratrol is only one of the possible grape-derived compounds that may partly underpin the beneficial effects of grapes on the central nervous system.